Hydrodynamics and liquid phase residence time distribution in mesh microreactor - Kulkarni, A. A.; Gorasia, A. K.; Ranade, V. V. (Chemical Engineering Science, 2007)
This paper is focused on the experimental analysis of residence time distribution and phase hold-up in a mesh microreactor. A microreactor, where a finely weaved mesh is sandwiched between two flat plates with specific inlets for gas and liquid, is proposed. The microvolumes formed upon sandwiching the mesh are totally connected and thus it yields a view of several interconnected microvolumes. This system is easy to build and does not need precision micromachining. A high-speed photographic analysis yielded the phase distribution for different mesh types over a wide range of operating gas and liquid flow rates. The RTD was studied by measuring the liquid phase conductivity at the outlet of the reactor. Channeling prevailed for mesh with smaller open area. The ADEM was used for fitting the tracer curves with tailing ends. The RTD and the image analysis for all the mesh types showed hysteresis when the gas flow rate was maintained constant and the liquid flow rate was gradually increased and then decreased. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: hydrodynamics; hysteresis; image analysis; microreactor; residence time distribution

Heterogeneous nucleation in citrate synthesis of AgNPs: effect of mixing and solvation dynamics - Deshpande, J. B.; Chakrabarty, S.; Kulkarni, A. A. (Chemical Engineering Journal, 2021)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">The heterogeneity issues in silver nanoparticle nucleation (Lee-Meisel route) have been investigated. The final polydispersity and sphericity of the nanoparticles in the Lee-Meisel scheme are shown to depend upon the early time dynamics of silver-citrate complexation. The formation of macromolecular intermediary complexes in the early stages of the reaction is visualized based on online DLS data, TEM analysis, and the mass balances of silver and citrate ions. The reversible complexation between citrate ions and silver citrate is shown to be the limiting step that governs the directional growth of the nanoparticles. The dynamics of the complexation of citrate are seen to form a very rapid step and intense mixing was required for the complexation to happen uniformly across the reaction. This specific observation is also confirmed from the MD simulations. Thus, to get particles of high sphericity, irrespective of the reaction concentration, temperature, or reactor geometry, the mixing time should be <4 s and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Da<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> ~ 0.1. Optimal mixing conditions for isotropic growth are suggested based on the reaction kinetics and are also demonstrated with experimental evidence.